ANALYSIS OF OPEN DEFECATION SITES AND PUBLIC-PRIVATE CONVENIENCES IN KANO METROPOLIS, NIGERIA - Farouk, M.U; Tukur, Y.M; Sarki, U.S (FUDMA Journal of Earth and Environmental Sciences, 2024)
Open defecation menace (ODM) has remained one of the challenging urban environmental problems and public health issues in many cities in Nigeria, including Kano Metropolis. This study aimed to analyze the spatial location of open defecation sites and public-private conveniences in Kano Metropolis, with a view to map and locate areas with high cases and identify the drivers of ODM in the area. Primary data methods were employed to facilitate the study. The coordinates of ODSs and PPCs were obtained using Global Positioning System (GPS). Availability sampling was used to sample 399 respondents, and a structured questionnaire was administered. The ArcMap environment of ArcGIS 10.7 was employed to map the spatial location of ODSs and PPCs; Nearest Neighbour Analysis was conducted to determine the pattern of the spatial distributions. Descriptive statistics was used to analyze drivers of ODM. The finding revealed that the majority (60%) and (57%) of ODSs and PPCs are located in Kumbotso, while Dala accounted for (12%) and (7%) the least. It was also revealed that the majority (43%) of the respondents indicated that the monetary aspect is a major driver of ODM, and the least (5%) indicated the availability of conveniences. The study concluded that socioeconomic factors, inadequate sanitation facilities, urban planning, and cultural norms shape the patterns of ODM. In addition, people residing within OPSs are exposed to vulnerable health conditions. It was recommended that public-private partnerships should be established in the area of mobile toilet facilities around marketplaces, roads, streets, and motor parks.